Yavorov Post Mortem - Велкова-Гайдаржиева, Антония (Poznańskie Studia Slawistyczne, 2019)
Yavorov Year of Mourning by Mikhail Nedelchev is a ritual book dedicated to the most scorching deadly love affair in the history of the Bulgarian intelligentsia. This text is not a traditional literary-historical one, but an intimate reconstruction of the intolerable tragedy of the pre-death Yavorov year. It is argued that the poet’s being is not in the world, it is a being in and with death. The superconsciousness of death is an intimate experience for Yavorov, an act of insight.